The use of normothermic liver preservation in combined liver and lung transplantation: A single‐center experience. Issue 9 (18th April 2022) - Shamaa, Tayseer M.; Shamaa, Omar; Crombez, Catherine; Konel, Jonathan M.; Kitajima, Toshihiro; Shimada, Shingo; Ivanics, Tommy; Mohamed, Adhnan; Collins, Kelly; Nagai, Shunji; Yoshida, Atsushi; Abouljoud, Marwan; et al.
Abstract : Combined liver and lung transplantation (CLLT) is indicated in patients with both end‐stage liver and lung disease. Ex‐situ normothermic machine perfusion (NMP) has been previously used for extended normothermic lung preservation in CLLT. We aim to describe our single‐center experience using ex‐situ NMP for extended normothermic liver preservation in CLLT. Four CLLTs were performed from 2019 to 2020 with the lung transplanted first for all patients. Median ex‐situ pump time for the liver was 413 min (IQR 400–424). Over a median follow‐up of 15 months (IQR 14–19), all patients were alive and doing well. Normothermic extended liver preservation is a safe method to allow prolonged cold ischemia using normothermic perfusion of the liver during CLLT. Abstract : This case series of 4 combined‐liver lung transplants finds that ex‐situ normothermic machine perfusion appears to be safe for extended liver preservation.